Biomechanics of Hard Tissues: Modeling, Testing, and Materials - Andreas, Öchsner; Waqar, Ahmed (Wiley-VCH, 2011)
This monograph assembles expert knowledge on the latest biomechanical modeling and testing of hard tissues, coupled with a concise introduction to the structural and physical properties of bone and cartilage. A strong focus lies on the current advances in understanding bone structure and function from a materials science perspective, providing practical knowledge on how to model, simulate and predict the mechanical behavior of bone. The book presents directly applicable methods for designing and testing the performance of artificial bones and joint replacements, while addressing innovative and safe approaches to stimulated bone regeneration essential for clinical researchers.